2022
DOI: 10.1038/s41433-022-02061-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on phenotype of primary rhegmatogenous retinal detachment

Abstract: BACKGROUND:To evaluate the influence of age on the clinical characteristics of primary rhegmatogenous retinal detachments (RRD). METHODS: We conducted a retrospective review of a prospectively collected dataset. Data regarding adult patients (aged 16-100 years) who had undergone primary RRD repair, were extracted from two online databases. Baseline demographics, preoperative clinical characteristics and surgical management details were collected. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…Mean age of all patients with RD in our cohort was 61 years; in the bilateral group, it was 55 years of age when the initial eye had an RD and 57 years for the subsequent eye. Recently, the BEAVRS and EURETINA VR RD Outcomes Group found that the risk for fellow eye RD decreased linearly with age [11]. Data from the present study, however, show a decreasing proportion of fellow eye RD only in the age groups over 50 years.…”
Section: Age Sex Lens Statuscontrasting
confidence: 83%
“…Mean age of all patients with RD in our cohort was 61 years; in the bilateral group, it was 55 years of age when the initial eye had an RD and 57 years for the subsequent eye. Recently, the BEAVRS and EURETINA VR RD Outcomes Group found that the risk for fellow eye RD decreased linearly with age [11]. Data from the present study, however, show a decreasing proportion of fellow eye RD only in the age groups over 50 years.…”
Section: Age Sex Lens Statuscontrasting
confidence: 83%
“…The greatest excess of male RRD overall was in the 50-70-year age range, accounting for approximately 65% of cases, whereas after 80 years no clear sex predominance can be detected, consistently with two recent large retrospective studies [21,22]. It has previously been suggested the male predominance relates to trauma, but we excluded RRD directly attributable to recent trauma.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study of 8133 eyes found up to 20% of primary RRDs occurred in those younger than 50 years, with the large majority (83%) being phakic. 18 The study also found that the younger cohort was significantly associated with myopia and exhibited a myopia-related RRD phenotype. By performing secondary SB after failed PR, these patients may not require PPV, thus avoiding the potential loss of accommodation and anisometropia associated with the ensuing cataract surgery that is commonly required after PPV.…”
Section: Discussionmentioning
confidence: 77%
“… 12 , 13 , 15 17 In particular, there is a lack of data comparing the success rates between SB and PPV as secondary procedures after failed PR. This is an important consideration given that a substantial proportion of patients with RRD may be young, myopic, and with a clear crystalline lens who are likely to require cataract surgery after PPV, 18 thus losing their ability to accommodate and potentially developing symptomatic anisometropia.…”
Section: Introductionmentioning
confidence: 99%